1986
DOI: 10.1007/bf01320308
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder dyskinesia in chronic acalculous cholecystitis

Abstract: To test the hypothesis that there is an early stage of cholesterol gallstone formation in man characterized by symptoms of chronic cholecystitis, poor gallbladder emptying, and biliary cholesterol crystals, we studied cholecystokinin-stimulated gallbladder emptying by DISIDA scintigraphy and examined bile for cholesterol crystals in symptomatic patients with normal oral cholecystography and gallbladder sonography. Of 36 patients studied, 16 had biliary cholesterol crystals; their mean 30-min gallbladder ejecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
2

Year Published

1989
1989
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 18 publications
0
26
0
2
Order By: Relevance
“…From a patho physiological point of view, it is suggested that endo genous CCK may be closely related to the etiology and development of pancreatitis, because CCK and its C-ter minal analogue caerulein have been reported to produce acute pancreatitis (9,10) or to worsen it (11) in experimen tal animals, and because pancreatitis patients frequently suffer from accompanying hypercholecystokininemia (12). It has also been reported that CCK may be implicat ed in diseases such as acute cholecystitis, biliary dyskine sia (13) and irritable bowel syndrome (14). In recent years, several CCK-A-receptor antagonists have been developed and used for evaluating the physio logical and pathophysiological roles of CCK.…”
mentioning
confidence: 99%
“…From a patho physiological point of view, it is suggested that endo genous CCK may be closely related to the etiology and development of pancreatitis, because CCK and its C-ter minal analogue caerulein have been reported to produce acute pancreatitis (9,10) or to worsen it (11) in experimen tal animals, and because pancreatitis patients frequently suffer from accompanying hypercholecystokininemia (12). It has also been reported that CCK may be implicat ed in diseases such as acute cholecystitis, biliary dyskine sia (13) and irritable bowel syndrome (14). In recent years, several CCK-A-receptor antagonists have been developed and used for evaluating the physio logical and pathophysiological roles of CCK.…”
mentioning
confidence: 99%
“…MK-329 was not only effective in CCK infusion, is present in a large proportion of patients inducing stasis in control animals, but clearly aggravated with cholesterol gallstones, neither the sequential events nor gallbladder stasis in animals on the 1% high-cholesterol diet, the overall influence of gallbladder stasis on the whole pro-as evidenced by the greatest reduction in gallbladder contraccess of stone formation is fully understood. 1,[5][6][7]11,17 Our re-tion (Table 2) and largest gallbladder fasting volume (Table cent report, 14 which showed that gallbladder stasis actually 1). This may explain why this group of animals had the lowers bile CSI, appeared to complicate this issue even fur-highest mucin levels on the gallbladder surface.…”
Section: Aid Hepa 0040mentioning
confidence: 90%
“…MK-329 markedly inhibited paired. 6 Unfortunately, all the patients in this study had chronic cholecystitis, a confounding factor, which in itself gallbladder contraction in vitro in response to CCK (at EC 100 , control: 3.6 { 0.5 vs. MK-329: 1.1 { 0.3 g; P õ .05) and could have adversely affected gallbladder motor function. 1,5,8 Ground squirrels fed a high-cholesterol diet form cholesincreased gallbladder fasting volume in vivo (control: 462 { 66 vs. MK-329: 1,004 { 121 mL; P õ .05).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…A study on acalculous biliary pain in humans was described by Brugge et al [9]in which patients with impaired gallbladder emptying, measured by cholescintigraphy, were also found to have cholesterol crystals in their bile. Additionally, normal emptying was found to correlate well with the absence of biliary cholesterol crystals.…”
Section: Discussionmentioning
confidence: 99%